Characterization of Novel Rhabdoviruses in Chinese Bats - Dong-Sheng Luo; Bei Li; Xu-Rui Shen; Ren-Di Jiang; Yan Zhu; Jia Wu; Yi Fan; Hervé Bourhy; Ben Hu; Xing-Yi Ge; Zheng-Li Shi; Laurent Dacheux (Viruses, 2021)
Bats, the second largest order of mammals worldwide, harbor specific characteristics such as sustaining flight, a special immune system, unique habits, and ecological niches. In addition, they are the natural reservoirs of a variety of emerging or re-emerging zoonotic pathogens. Rhabdoviridae is one of the most diverse families of RNA viruses, which consists of 20 ecologically diverse genera, infecting plants, mammals, birds, reptiles, and fish. To date, three bat-related genera are described, named Lyssavirus, Vesiculovirus, and Ledantevirus. However, the prevalence and the distribution of these bat-related rhabdoviruses remain largely unknown, especially in China. To fill this gap, we performed a large molecular retrospective study based on the real-time reverse transcription polymerase chain reaction (RT-qPCR) detection of lyssavirus in bat samples (1044 brain and 3532 saliva samples, from 63 different bat species) originating from 21 provinces of China during 2006–2018. None of them were positive for lyssavirus, but six bat brains (0.6%) of Rhinolophus bat species, originating from Hubei and Hainan provinces, were positive for vesiculoviruses or ledanteviruses. Based on complete genomes, these viruses were phylogenetically classified into three putative new species, tentatively named Yinshui bat virus (YSBV), Taiyi bat virus (TYBV), and Qiongzhong bat virus (QZBV). These results indicate the novel rhabdoviruses circulated in different Chinese bat populations.